Aerobic Exercise Ameliorates Myocardial Inflammation, Fibrosis and Apoptosis in High-Fat-Diet Rats by Inhibiting P2X7 Purinergic Receptors - Chen, Xudong; Li, Haiyan; Wang, Kangwei; Liang, Xiaohe; Wang, Weiqi; Hu, Xiaokang; Huang, Zhouqing; Wang, Yonghua (Frontiers in Physiology, 2019)
Background: High-fat-diet (HFD)-induced obesity is associated with chronic low-grade inflammation. P2X7 purinergic receptors (P2X7R) are key regulators of inflammasome activation. The benefits of exercise are partly attributed to its anti-inflammatory effect, but whether it regulates P2X7R expression to improve remodeling in cardiac myocytes treated by HFD is not completely clarified. Methods: Three groups of Sprague-Dawley rats were studied: (1) control group, (2) HFD group, and (3) HFD+exercise group. H9c2 were pretreated with or without A438079 and then exposed to 200 μM palmitic acid (PA) for 24 h. The levels of mRNA and protein were measured by real-time PCR and Western blot, respectively. Masson staining and hematoxylin-eosin staining were used to identify remodeling of the heart. The concentration of IL-1β in serum or supernatants were measured by ELISA. Results: In vivo, collagen deposition and the number of cells that were disordered significantly increased in the hearts of the HFD group compared to the control group. However, exercise markedly reversed these changes in the myocardium, and the same trends were observed for MMP9, collagen I and TGF-β expression. Notably, the expression of P2X7R, NLRP3, caspase-1 in the hearts, and serum IL-1β level were also greatly upregulated in the heart of the HFD rats, and all these changes were ameliorated in the HFD+EX group. As expected, exercise also reduced the number of TUNEL-positive cells, which was consistent with the caspase-3, Bax and Bcl-2 results. Moreover, exercise reduced body weight and blood lipid concentrations in the HFD diet rats. In vitro, we observed that the hallmark of fibrosis, inflammation and apoptosis in H9c2 enhanced by PA, and the P2X7R inhibitor treatment significantly reduced the expression of the NLRP3, caspase-1 suppressed the secretion of IL-1β of H9c2 cells, inhibited collagen I, TGF-β, MMP9, Bax, caspase-3 levels and increased the expression of Bcl-2, compared with the PA group. In addition, a decrease of the number of TUNEL-positive cells by A438079 further support that cardiomyocytes apoptosis could be inhibited. Conclusion: Aerobic exercise reversed the cardiac remodeling via the reduction of inflammation, fibrosis and apoptosis in obese rats, at least in part through inhibiting P2X7R expression in cardiomyocytes.